Mobile Relay Assisted Handover for LTE System in High-Speed Railway - Qian Xingyu; Wu Hao (2012 International Conference on Control Engineering and Communication Technology, 2012)
A handover scheme with the assist of a Mobile Relay Station (MRS) and dual antennas is proposed for high speed railway private cellular network in this paper. After introducing a MRS, the Radio Resource Management (RRM) of the railway wireless communication system, e.g. handover process, should be made corresponding changes. This paper integrates the relative handover signaling, and employs a MRS and dual-antenna mechanism to improve the quality of the received signal and to enhance handover performance. Furthermore, bi-casting is adopted to eliminate data forwarding delay between the serving evolved NodeB (eNB) and the target one. The proposed scheme is evaluated by simulation in terms of handover outage probability and communication interruption probability. The results show the proposed handover scheme can reduce outage probability and provide the seamless experience for users on board compared to the standard LTE handover scheme.